Development of a Management Strategy for Forming an Innovation Ecosystem of the University - Blagorazumnaya, Olga; Balan, Igor; Israeli, Milana; Lupu, Constantin (Acta Universitatis Danubius. Œconomica, 2024)
At present, universities are experiencing a significant shift in their strategic focus, acknowledging the imperative to adapt and utilize knowledge more effectively in the realm of innovation for both the market and society. Entrepreneurial universities are strategically positioned as generators and disseminators of new knowledge, orchestrators of interdisciplinary initiatives, and catalysts in forging connections between academia and industries. They formulate a strategy for creating and nurturing an ecosystem tailored to their chosen scenario, whether the university acts as the instigator of an innovation ecosystem (IE) or as a participant in an existing one. The objective is to streamline the dissemination, application, and utilization of knowledge and technologies. In this context, the authors propose a systematic approach for all stakeholders in the innovation ecosystem domain. This involves progressing through successive stages, including conducting theoretical and practical research, devising a strategy formation algorithm, and outlining the content of strategic scenarios. The suggested algorithm holds a pivotal role in shaping a university’s innovation ecosystem and comprises specific elements such as identifying and analyzing constraining research factors, establishing strategic goals, generating and deliberating on strategic scenarios for the formation and development of the Innovation Ecosystem at the University (IEU), and evaluating effects with subsequent strategy adjustments. The examination of scenarios is contextualized within the framework of goals, objectives, and strategic activities.